Shipwreck and Psychosis: Sheila Fugard's The Castaways. Issue 3 (3rd April 2022) - Titlestad, Michael
Abstract : Sheila Fugard's The Castaways (1972) is neglected in South African literary historiography because its experimental modernism was at odds with the emphasis in the 1970s on politically committed literature. Further, its dialogism and preoccupation with the spiritual inflection of whiteness make it, at times, recondite. Fugard resets the events of the wreck of the Indiaman Grosvenor in 1782 as the hallucinated interiority of Christiaan Jordan, an escaped inmate of a psychiatric institution. The destruction of the ship and fate of her castaways (and contemporary parallels) constitute the language of his psychosis. This inward turn of shipwreck narrative is occasionally apparent in the historical and literary archive but is developed most fully and resonantly in The Castaways. While this essay considers and contextualizes the novel, it also places in counterpoint a fragmented account of my obsession with shipwreck and personal history of psychosis and dissociation. The two levels of writing are intended to set up eddies in a watery relation.